ANALISIS POTENSI BENCANA LONGSOR MENGGUNAKAN METODE KINEMATIK DI DESA JABUNGAN, KOTA SEMARANG - Perkasa, Leony Isda; Dirostrimila, Najwa Humaira; Soputan, Puspo Anggreiny Putri; Widiarso, Dian Agus (PPSDM Geominerba, 2024)
Research area is a residential area located in Jabungan, Banyumanik, Semarang, Central Java. The research focuses on analyzing the potential of landslides that can occur. The research slope is located with residential areas and roads. Based on the potential damage that can occur if the slope slides become the background of this study. Near the research location which is a residential area and roads, the slope stability factor needs to be considered because a stable slope causes the slope to be safe and there is less possibility of landslides. Landslide is the movement of the soil mass or the expanse of experience plane or a shear surface plane. The types of landslides have a relationship with the geological structures that cause discontinuities in a rock mass. One of the steps to determine the possibility of landslides from a slope is the kinematic analysis method. Kinematic analysis is carried out with the aim of knowing the types of landslides that may occur. After doing kinematic analysis, the slope is possible for landslides to occur. By knowing the potential of landslides, it can be used as a basis for mitigation so that landslides not occur in the area that can cause losses.